Negative electrode for lithium secondary battery and lithium secondary battery comprising negative electrode

KR103031642B1Active Publication Date: 2026-10-13LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020230080500
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-23
Filing Date
2023-06-22
Publication Date
2026-10-13
Estimated Expiration
2043-06-22

Smart Images

  • Figure 112023068945371-PAT00001_ABST
    Figure 112023068945371-PAT00001_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode for a lithium secondary battery and a lithium secondary battery comprising the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0076794 filed with the Korean Intellectual Property Office on June 23, 2022, the entire contents of which are incorporated herein.

[0002] The present application relates to a negative electrode for a lithium secondary battery and a lithium secondary battery comprising the negative electrode. Background Technology

[0003] Due to the rapid increase in the use of fossil fuels, there is a growing demand for alternative or clean energy. As part of this effort, the fields of power generation and energy storage utilizing electrochemical reactions are the most actively researched.

[0004] Currently, a representative example of an electrochemical device utilizing such electrochemical energy is the secondary battery, and its scope of application is steadily expanding.

[0005] With the increasing technological development and demand for mobile devices, the demand for secondary batteries as an energy source is rapidly rising. Among these secondary batteries, lithium-ion batteries, which possess high energy density and voltage, long cycle life, and low self-discharge rates, have been commercialized and are widely used. Furthermore, active research is being conducted on methods to manufacture high-density electrodes with higher energy density per unit volume for use in such high-capacity lithium-ion batteries.

[0006] Generally, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and extracts lithium ions from the positive electrode, and silicon-based particles with a large discharge capacity may be used as the negative electrode active material.

[0007] In particular, driven by the recent demand for high-density energy batteries, active research is being conducted on methods to increase capacity by using silicon-based compounds, such as Si / C or SiOx, as anode active materials. These compounds possess a capacity more than 10 times greater than that of graphite-based materials. However, while silicon-based compounds—high-capacity materials—offer superior capacity characteristics compared to conventionally used graphite, their volume expands rapidly during the charging process, disrupting conductive pathways and degrading battery performance; consequently, capacity drops from the outset. Furthermore, silicon-based anodes do not achieve uniform lithium ion charging along the depth of the anode during repeated charge and discharge cycles; instead, reactions proceed at the surface, accelerating surface degradation. Consequently, performance improvements are required in terms of battery cycleability.

[0008] Furthermore, when fabricating a cathode using silicon-based active materials, it is important that the pore structure of the cathode is simple, and it is known that for a cathode using silicon-based active materials, better tortuosity is advantageous for diffusion resistance. However, when the porosity is unconditionally increased to improve tortuosity, the contact points with the cathode current collector layer decrease, which reduces the adhesion to the cathode current collector layer and causes delamination, resulting in a problem of reduced lifespan characteristics.

[0009] Although various studies are underway to address the aforementioned problems, their application is limited as they can actually degrade battery performance. Consequently, there are still limitations to the commercialization of negative electrode batteries with high silicon-based compound content. Furthermore, as the proportion of silicon-based active material in the silicon-based active material layer increases, reactions with lithium ions become concentrated on the negative electrode surface, leading to damage to the silicon-based active material on the surface and a decrease in lifespan characteristics.

[0010] Therefore, even when using silicon-based compounds as active materials, it is necessary to develop a lithium secondary battery that improves the tortuosity of the negative electrode during charge and discharge cycles while simultaneously possessing excellent adhesion to the negative electrode current collector layer. Prior art literature

[0011] Japanese Published Patent Application No. 2009-080971 The problem to be solved

[0012] In the case of conventional carbon-based cathodes, there were no issues related to volume expansion, so controlling the porosity of the carbon-based cathode active material layer or the adhesion to the current collector layer was not a problem.

[0013] However, to secure capacity characteristics, the negative electrode is being used by changing from a carbon-based active material to a silicon-based active material; although general silicon-based active materials (such as SiO) have more severe volume expansion issues than carbon-based active materials, no problems arising from this have occurred.

[0014] However, recently, Pure Si active materials have been used among silicon-based active materials to maximize capacity characteristics and ensure rapid charging; in this case, severe volume expansion has led to a problem where lifespan characteristics deteriorate due to delamination from the negative electrode current collector layer.

[0015] Accordingly, the present application relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the negative electrode, which can improve cycle performance by using a silicon-based active material in the negative electrode, improving tortuosity to prevent electrode surface degradation during charge and discharge cycles, and further improving adhesion with the negative electrode current collector layer. means of solving the problem

[0016] One embodiment of the present specification is a negative electrode for a lithium secondary battery comprising: a negative current collector layer; a primer coating layer comprising a primer coating layer composition provided on one or both sides of the negative current collector layer; and a negative active material layer provided on the opposite side of the primer coating layer that contacts the negative current collector layer; wherein the negative active material layer comprises a negative active material composition comprising a silicon-based active material; a negative conductive material; and a negative binder, and the silicon-based active material comprises SiOx (x=0) and SiOx (0 <x<2)로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 실리콘계 활물질 100 중량부 기준 상기 SiOx (x=0)를 95 중량부 이상 포함하며, 상기 프라이머 코팅층 조성물은 바인더; 및 도전재;로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 음극 활물질층의 공극률(porosity)이 50% 이상이며, 상기 음극 활물질층에 포함되는 실리콘계 활물질의 D50 입도가 5μm 이상인 것인 리튬 이차 전지용 음극을 제공한다.

[0017] In another embodiment, a lithium secondary battery is provided comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte. Effects of the invention

[0018] A negative electrode for a lithium secondary battery according to one embodiment of the present invention is characterized in that the active material layer has a single-layer structure, the energy density of the negative electrode is increased by increasing the content of silicon-based active material in the negative electrode active material layer, and the tortuosity is improved by simplifying the pore structure so that the range of particle size and porosity of the silicon-based active material satisfies the range according to the present application.

[0019] Consequently, the negative active material layer undergoes significant volume expansion during charging and discharging, which can cause it to detach from the negative current collector as the cycle progresses. Additionally, to achieve high energy density, the amounts of negative conductive material and negative binder are minimized, which can reduce the number of contact points with the negative current collector. The main objective of the present invention is to resolve these problems by coating a primer coating layer, comprising a primer coating layer composition satisfying specific composition and content, onto the negative current collector layer.

[0020] In other words, the main feature of the present invention is that it can maximize the high energy density and capacity characteristics, which are advantages of silicon-based cathodes, while simultaneously addressing existing problems by controlling the range of porosity of the cathode active material layer and applying a primer coating layer, thereby improving lifespan characteristics.

[0021] Ultimately, the negative electrode for a lithium secondary battery according to the present invention is characterized by maximizing capacity characteristics by using a silicon-based active material, and having excellent output and lifespan characteristics by using a primer coating layer having a specific composition to improve adhesion to the negative electrode current collector while the negative electrode active material layer satisfies a specific porosity range to simplify the pore structure. Brief explanation of the drawing

[0022] FIG. 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to one embodiment of the present application. Specific details for implementing the invention

[0023] Before describing the present invention, we will first define some terms.

[0024] In this specification, when a part is described as "comprising" a certain component, it means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0025] In this specification, 'p to q' means a range of 'p or more and q or less'.

[0026] In this specification, "specific surface area" is measured by the BET method, specifically calculated from the amount of nitrogen gas adsorbed at a liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Japan. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above measurement method.

[0027] In this specification, "Dn" refers to the particle size distribution and represents the particle size at the n% point of the cumulative distribution of the number of particles according to particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative distribution of the number of particles according to particle size, D90 is the particle size at the 90% point of the cumulative distribution of the number of particles according to particle size, and D10 is the particle size at the 10% point of the cumulative distribution of the number of particles according to particle size. Meanwhile, the particle size distribution can be measured using the laser diffraction method. Specifically, after dispersing the powder to be measured in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) and the difference in diffraction patterns according to particle size is measured as the particles pass through the laser beam to calculate the particle size distribution.

[0028] In this specification, the meaning that a polymer contains a monomer in monomer units means that the monomer participates in a polymerization reaction and is included as a repeating unit within the polymer. In this specification, when it is stated that a polymer contains a monomer, this is interpreted as the same as the polymer containing the monomer in monomer units.

[0029] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers unless specified as "homopolymer."

[0030] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are polystyrene equivalent molecular weights measured by gel permeation chromatography (GPC), using commercially available monodisperse polystyrene polymers of various degrees of polymerization (standard samples) for molecular weight measurement as standard materials. In this specification, the term "molecular weight" means weight-average molecular weight unless otherwise specified.

[0031] Hereinafter, the present invention will be described in detail with reference to the drawings so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in various different forms and is not limited to the description below.

[0032] One embodiment of the present specification is a negative electrode for a lithium secondary battery comprising: a negative current collector layer; a primer coating layer comprising a primer coating layer composition provided on one or both sides of the negative current collector layer; and a negative active material layer provided on the opposite side of the primer coating layer that contacts the negative current collector layer; wherein the negative active material layer comprises a negative active material composition comprising a silicon-based active material; a negative conductive material; and a negative binder, and the silicon-based active material comprises SiOx (x=0) and SiOx (0 <x<2)로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 실리콘계 활물질 100 중량부 기준 상기 SiOx (x=0)를 95 중량부 이상 포함하며, 상기 프라이머 코팅층 조성물은 바인더; 및 도전재;로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 음극 활물질층의 공극률(porosity)이 50% 이상이며, 상기 음극 활물질층에 포함되는 실리콘계 활물질의 D50 입도가 5μm 이상인 것인 리튬 이차 전지용 음극을 제공한다.

[0033] The negative electrode for a lithium secondary battery according to the present application is characterized by having a primer coating layer having a specific composition in order to take advantage of an electrode that uses a high content of silicon particles as a single-layer active material, while simultaneously solving the disadvantages of such an electrode, such as the problem of simplification of the negative electrode pore structure, the problem of improving adhesion with the negative electrode current collector layer, and the problem of output characteristics.

[0034] FIG. 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to one embodiment of the present application. Specifically, a negative electrode (100) for a lithium secondary battery including a primer coating layer (20) and a negative active material layer (30) on one surface of a negative current collector layer (10) can be seen. FIG. 1 shows that the negative active material layer and the primer coating layer are formed on one surface, but they may be included on both surfaces of the negative current collector layer. When included on both surfaces, the primer coating layer may be formed on both surfaces or on one surface of the negative current collector layer.

[0035] The negative electrode for a lithium secondary battery according to the present invention will be described in more detail below.

[0036] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, comprising: a negative current collector layer; a primer coating layer provided on one or both sides of the negative current collector layer; and a negative active material layer provided on the opposite side of the primer coating layer that contacts the negative current collector layer.

[0037] In one embodiment of the present application, the negative current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative current collector layer is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloy may be used. In addition, fine irregularities may be formed on the surface to strengthen the bonding strength of the negative active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven body, etc.

[0038] In one embodiment of the present application, the thickness of the negative current collector layer may be 1 μm or more and 100 μm or less.

[0039] However, the thickness may vary depending on the type and application of the cathode used, and is not limited thereto.

[0040] In one embodiment of the present application, the cathode active material layer comprises a cathode active material layer composition including a silicon-based active material; a cathode conductive material; and a cathode binder.

[0041] In one embodiment of the present application, the silicon-based active material comprises a silicon-based active material having silicon particles with a silicon particle size distribution of 0.01 μm or more and 50 μm or less, and provides a negative electrode for a lithium secondary battery in which the silicon-based active material included in the negative electrode active material layer has a D50 particle size of 5 μm or more.

[0042] In one embodiment of the present application, the silicon-based active material is SiOx (x=0) and SiOx (0 <x<2)로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 실리콘계 활물질 100 중량부 기준 상기 SiOx (x=0)를 95 중량부 이상 포함할 수 있다.

[0043] In one embodiment of the present application, the silicon-based active material is SiOx (x=0) and SiOx (0 <x<2)로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 실리콘계 활물질 100 중량부 기준 상기 SiOx (x=0)를 95 중량부 이상, 바람직하게는 SiOx (x=0)를 97 중량부 이상, 더욱 바람직하게는 99 중량부 이상을 포함할 수 있고, 100 중량부 이하를 포함할 수 있다.

[0044] In one embodiment of the present application, the silicon-based active material may particularly use pure silicon (Si) particles. Using pure silicon (Si) as the silicon-based active material means that, when the silicon-based active material is based on 100 parts by weight of the total as described above, pure Si particles (SiOx (x=0)) that are not bonded with other particles or elements are included in the above range.

[0045] In one embodiment of the present application, the silicon-based active material may be composed of SiOx (x=0).

[0046] The negative electrode for a lithium secondary battery according to the present application comprises the aforementioned silicon-based active material in the negative electrode active material layer, specifically comprising pure silicon particles containing 95 parts by weight or more of SiOx (x=0). At this time, when the pure silicon particles are included in a high content, the capacity characteristics are excellent, and to solve the problem of reduced lifespan due to the simplification of the pore structure resulting therefrom, the above problem is solved by including a primer coating layer according to the present invention.

[0047] Meanwhile, the average particle size (D50) of the silicon-based active material of the present invention may be 3㎛ to 10㎛, specifically 4㎛ to 8㎛, and more specifically 5㎛ to 7㎛. When the average particle size falls within the above range, the specific surface area of ​​the particles is within a suitable range, and the viscosity of the cathode slurry is formed within an appropriate range. Accordingly, the dispersion of particles constituting the cathode slurry becomes smooth. In addition, since the size of the first cathode active material has a value greater than or equal to the lower limit range, the contact area between the silicon particles and the conductive materials is excellent due to the composite composed of the conductive material and the binder within the cathode slurry, which increases the likelihood of the conductive network continuing and thus increases the capacity retention rate. Meanwhile, when the average particle size satisfies the above range, excessively large silicon particles are excluded, and the surface of the cathode is formed smoothly, thereby preventing current density non-uniformity during charging and discharging.

[0048] In particular, the negative electrode for a lithium secondary battery according to the present application satisfies a porosity of 50% or more of the negative electrode active material layer.

[0049] The above-mentioned porosity control affects the overall composition and content of the negative electrode active material layer composition, but is mainly influenced by the D50 particle size of the silicon-based active material included in the negative electrode active material layer composition.

[0050] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the silicon-based active material included in the negative electrode active material layer has a D50 particle size of 5 μm or more.

[0051] In another embodiment, the D50 particle size of the silicon-based active material included in the negative electrode active material layer may be 6 μm or more, preferably 7 μm or more, more preferably 8 μm or more, and may satisfy a range of 15 μm or less.

[0052] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the silicon-based active material included in the negative electrode active material layer has a D50 particle size of 8 μm or more and 15 μm or less.

[0053] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the porosity of the negative electrode active material layer is 60% or more and 90% or less.

[0054] In one embodiment of the present application, the porosity of the negative electrode active material layer may be 50% or more, preferably 60% or more, and may satisfy 90% or less, preferably 80% or less.

[0055] The negative electrode for a lithium secondary battery according to the present application satisfies the ranges of particle size distribution and porosity as described above, and by satisfying the porosity within the above range, it improves diffusion resistance by improving the phenomenon where the reaction between lithium ions and silicon-based active materials is concentrated only on the surface through the simplification of the pore structure. Furthermore, the problem at this time is addressed by including a primer coating layer of a specific composition to improve adhesion with the negative electrode current collector layer, thereby increasing adhesion even when charging / discharging cycles are continued, and thus having enhanced lifespan characteristics.

[0056] In one embodiment of the present application, the silicon-based active material generally has a characteristic BET surface area. The BET surface area of ​​the silicon-based active material is preferably 0.01 m² 2 / g to 150.0 m 2 / g, more preferably 0.1m 2 / g to 100.0 m 2 / g, particularly preferably 0.2m 2 / g to 80.0 m 2 / g, most preferably 0.2m 2 / g to 18.0 m 2 / g. The BET surface area is measured according to DIN 66131 (using nitrogen).

[0057] In one embodiment of the present application, the silicon-based active material may exist, for example, in a crystalline or amorphous form and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or exist in the form of a silicon-containing film or coating.

[0058] In one embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the degree of sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0059] In the present application, the circularity is determined by the following formula 1, where A is the area and P is the boundary line.

[0060] [Equation 1]

[0061] 4πA / P 2

[0062] In one embodiment of the present application, the silicon-based active material may be 80 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition.

[0063] In another embodiment, the silicon-based active material may be 80 parts by weight or more, preferably 85 parts by weight or more, based on 100 parts by weight of the negative electrode active material layer composition, and may satisfy 99 parts by weight or less, preferably 97 parts by weight or less, more preferably 95 parts by weight or less.

[0064] The negative electrode active material layer composition according to the present application has the effect of improving capacity characteristics by using a silicon-based active material with significantly high capacity within the above range. In particular, by adjusting the range of the silicon-based active material included in the negative electrode active material layer to the above range, the capacity performance of the entire negative electrode is not degraded, and the problems of surface degradation during charging and discharging, lifespan characteristics, and securing conductive pathways are resolved.

[0065] Conventionally, it was common practice to use only graphite-based compounds as negative electrode active materials; however, with the recent rise in demand for high-capacity batteries, there have been increasing attempts to mix in silicon-based compounds to increase capacity. Nevertheless, silicon-based compounds have a limitation in that their volume expands rapidly during the charging and discharging process, damaging the conductive pathways formed within the negative electrode active material layer and actually degrading battery performance.

[0066] In addition, when a silicon-based active material of a certain particle size is included within the range to control the porosity range as described above, a problem exists in which output characteristics are degraded and lifespan characteristics are reduced because a conductive path is not secured due to volume expansion during charging and discharging.

[0067] Accordingly, in one embodiment of the present application, the cathode conductive material may include one or more selected from the group consisting of a point conductive material; a linear conductive material; and a planar conductive material.

[0068] In one embodiment of the present application, the cathode conductive material may be any material generally used in the art without limitation, and specifically is selected from the group consisting of point conductive materials; planar conductive materials; and linear conductive materials.

[0069] In one embodiment of the present application, the dot-shaped conductive material can be used to improve conductivity of the cathode and refers to a conductive material having a dot shape or a sphere that is conductive without causing chemical changes. Specifically, the dot-shaped conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, Farnes black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably may include carbon black in terms of achieving high conductivity and excellent dispersibility.

[0070] In one embodiment of the present application, the point-shaped conductive material has a BET specific surface area of ​​40 m² 2 / g or more 70m 2 It may be less than / g, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 It may be less than / g.

[0071] In one embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0072] In one embodiment of the present application, the planar conductive material can be expressed as a plate-shaped conductive material or a bulk-shaped conductive material, which can improve conductivity by increasing surface contact between silicon particles within the cathode and simultaneously suppress the interruption of the conductive path due to volume expansion.

[0073] In one embodiment of the present application, the planar conductive material may comprise at least one selected from the group consisting of plate-shaped graphite, graphene, graphene oxide, and graphite flakes, and preferably may be plate-shaped graphite.

[0074] In one embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the above range is satisfied, dispersion is easy without causing an excessive increase in the viscosity of the cathode slurry due to the sufficient particle size. Therefore, when dispersion is performed using the same equipment and time, the dispersion effect is excellent.

[0075] In one embodiment of the present application, the planar conductive material provides a cathode composition in which D10 is 0.5 μm or more and 1.5 μm or less, D50 is 2.5 μm or more and 3.5 μm or less, and D90 is 7.0 μm or more and 15.0 μm or less.

[0076] In one embodiment of the present application, the planar conductive material may be a high specific surface area planar conductive material having a high BET specific surface area; or a low specific surface area planar conductive material.

[0077] In one embodiment of the present application, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area may be used without limitation as the planar conductive material; however, since the planar conductive material according to the present application may be affected to some extent by dispersion in electrode performance, it may be particularly preferable to use a planar conductive material with a low specific surface area that does not cause problems with dispersion.

[0078] In one embodiment of the present application, the planar conductive material has a BET specific surface area of ​​5 m² 2 It can be more than / g.

[0079] In another embodiment, the planar conductive material has a BET specific surface area of ​​5m²2 / g or more than 500m 2 It may be less than / g, preferably 5m 2 / g or more than 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 It may be less than / g.

[0080] In another embodiment, the planar conductive material is a high specific surface area planar conductive material, and has a BET specific surface area of ​​50 m² 2 / g or more than 500m 2 / g or less, preferably 80m 2 / g or more than 300m 2 / g or less, more preferably 100m 2 / g or more than 300m 2 It can satisfy a range of / g or less.

[0081] In another embodiment, the planar conductive material is a low specific surface area planar conductive material, and the BET specific surface area is 5m² 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 It can satisfy a range of / g or less.

[0082] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may comprise a plurality of carbon nanotube units. Specifically, "bundle type" here refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged in parallel or intertwined with the axes along the length direction of the carbon nanotube units in substantially the same orientation, unless otherwise noted. The carbon nanotube units have a graphite sheet having a cylindrical shape with a nano-sized diameter and an sp2 bonding structure. Depending on the angle and structure in which the graphite sheet is rolled, it may exhibit conductive or semiconductor properties. Compared to entangled type carbon nanotubes, the bundled carbon nanotubes described above can be uniformly dispersed during cathode manufacturing and smoothly form a conductive network within the cathode, thereby improving the conductivity of the cathode.

[0083] In one embodiment of the present application, the cathode conductive material may satisfy an amount of 0.01 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the cathode active material layer composition.

[0084] In another embodiment, the cathode conductive material may be 0.01 parts by weight or more and 40 parts by weight or less, preferably 0.1 parts by weight or more and 30 parts by weight or less, based on 100 parts by weight of the cathode active material layer composition, and more preferably 0.5 parts by weight or more and 25 parts by weight or less.

[0085] In one embodiment of the present application, when the cathode conductive material comprises a linear conductive material alone, it may satisfy 0.01 parts by weight or more and 5 parts by weight or less based on 100 parts by weight of the cathode active material layer composition.

[0086] In another embodiment, when the cathode conductive material comprises a linear conductive material alone, the amount may be 0.01 parts by weight or more and 5 parts by weight or less, preferably 0.03 parts by weight or more and 3 parts by weight or less, based on 100 parts by weight of the cathode active material layer composition, and more preferably 0.1 parts by weight or more and 2 parts by weight or less.

[0087] In one embodiment of the present application, the cathode conductive material comprises a point-type conductive material; a planar conductive material; and a linear conductive material, wherein the ratio of the point-type conductive material:planar conductive material:linear conductive material may satisfy a ratio of 1:1:0.01 to 1:1:1.

[0088] In one embodiment of the present application, the point-shaped conductive material may satisfy a range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the cathode conductive material.

[0089] In one embodiment of the present application, the planar conductive material may satisfy a range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the cathode conductive material.

[0090] In one embodiment of the present application, the linear conductive material may satisfy a range of 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 8 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the cathode conductive material.

[0091] In one embodiment of the present application, the cathode conductive material may include a linear conductive material and a planar conductive material.

[0092] In one embodiment of the present application, the cathode conductive material comprises a linear conductive material and a planar conductive material, and the ratio of the linear conductive material to the planar conductive material may satisfy 0.01:1 to 0.1:1.

[0093] In one embodiment of the present application, the negative electrode conductive material specifically comprises a linear conductive material and a planar conductive material, each satisfying the composition and ratio, so that the lifespan characteristics of the existing lithium secondary battery are not significantly affected, and the number of charge and discharge points increases, resulting in excellent output characteristics at a high C-rate.

[0094] The cathode conductive material according to the present application has a completely separate composition from the anode conductive material applied to the anode. That is, the cathode conductive material according to the present application serves to hold the contact points between silicon-based active materials, which undergo significant volume expansion of the electrodes due to charging and discharging, whereas the anode conductive material serves as a buffer during rolling and provides some conductivity; thus, their composition and roles are completely different from those of the cathode conductive material of the present invention.

[0095] Furthermore, the cathode conductive material according to the present application is applied to silicon-based active materials and has a completely different composition from that of a conductive material applied to graphite-based active materials. That is, a conductive material used in an electrode having a graphite-based active material simply has particles smaller than the active material, thereby providing improved output characteristics and some conductivity; thus, its composition and role are completely different from that of a cathode conductive material applied together with a silicon-based active material as in the present invention.

[0096] In one embodiment of the present application, the cathode binder may comprise at least 1 part by weight and no more than 20 parts by weight based on 100 parts by weight of the cathode active material layer composition.

[0097] In another embodiment, the cathode binder may satisfy a range of 1 part by weight or more and 20 parts by weight or less, preferably 2 parts by weight or more and 15 parts by weight or less, based on 100 parts by weight of the cathode active material layer composition, more preferably 3 parts by weight or more and 15 parts by weight or less.

[0098] In one embodiment of the present application, the cathode binder may comprise at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogens thereof are substituted with Li, Na, or Ca, etc., and may also comprise various copolymers thereof.

[0099] The cathode binder according to one embodiment of the present application serves to hold the active material and the conductive material to prevent distortion and structural deformation of the cathode structure during volume expansion and relaxation of the cathode silicon-based active material. Any general binder that satisfies the above role can be applied, specifically a water-based binder can be used, and more specifically, a PAM-based binder can be used.

[0100] In one embodiment of the present application, the primer coating layer comprises a primer coating layer composition provided on one or both sides of the cathode current collector layer, wherein the primer coating layer composition may comprise one or more selected from the group consisting of a binder and a conductive material.

[0101] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the thickness of the primer coating layer is 1 nm or more and 1 μm or less.

[0102] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the binder is in an amount of 10 parts by weight or more and 100 parts by weight or less based on 100 parts by weight of the primer coating layer composition.

[0103] The primer coating layer composition according to the present application may include a binder alone.

[0104] The primer coating layer composition according to the present application may include a binder and a conductive material.

[0105] At this time, the present application provides a negative electrode for a lithium secondary battery in which the binder is 10 parts by weight or more and 100 parts by weight or less based on 100 parts by weight of the primer coating layer composition according to the present application.

[0106] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the adhesion force of the surface of the negative electrode active material layer in contact with the primer coating layer satisfies 100gf / 5mm or more and 500gf / 5mm or less under conditions of 25℃ and atmospheric pressure.

[0107] In another embodiment, the adhesion strength of the surface of the cathode active material layer in contact with the primer coating layer can satisfy 300gf / 5mm or more and 500gf / 5mm or less, preferably 300gf / 5mm or more and 450gf / 5mm or less, and more preferably 350gf / 5mm or more and 430gf / 5mm or less, under conditions of 25℃ and atmospheric pressure.

[0108] The above adhesive strength was measured using a Peel Strength meter with 3M 9070 tape at a speed of 5 mm / s at a 90° angle. Specifically, one side of the negative electrode active material layer of the negative electrode for the lithium secondary battery is adhered to one side of a slide glass (3M 9070 tape) to which an adhesive film is attached. Subsequently, it is adhered by reciprocating 5 to 10 times with a 2 kg rubber roller, and the adhesive strength (peel strength) is measured at a speed of 5 mm / s at a 90° angle. At this time, the adhesive strength can be measured under conditions of 25° and atmospheric pressure.

[0109] Specifically, the adhesion strength was measured on a 5mm x 15cm electrode at 25℃ under atmospheric pressure conditions.

[0110] In one embodiment of the present application, atmospheric pressure may mean pressure in a state where no specific pressure is applied or lowered, and may be used interchangeably with atmospheric pressure. Generally, it may be expressed as 1 atmosphere.

[0111] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.

[0112] In one embodiment of the present application, a lithium secondary battery is provided comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0113] A secondary battery according to one embodiment of the present specification may particularly include a negative electrode for a lithium secondary battery as described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is identical to the negative electrode described above. Since the negative electrode has been described above, a detailed description thereof is omitted.

[0114] The above positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and comprising the positive electrode active material.

[0115] In the above-mentioned positive electrode, the positive electrode current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the above-mentioned positive electrode current collector may typically have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesion of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0116] The above-mentioned positive electrode active material may be a commonly used positive electrode active material. Specifically, the above-mentioned positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; lithium iron oxide such as LiFe3O4; or a compound with the chemical formula Li 1+c1 Mn 2-c1 Lithium manganese oxides such as O4 (0≤c1≤0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7, etc.; chemical formula LiNi 1-c2 M c2 Ni-site type lithium nickel oxide represented by O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, satisfying 0.01≤c2≤0.3); chemical formula LiMn 2-c3 M c3Examples include lithium manganese composite oxides represented by O2 (where M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, satisfying 0.01≤c3≤0.1) or Li2Mn3MO8 (where M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); and LiMn2O4 in which a portion of the Li in the chemical formula is substituted with alkaline earth metal ions, but are not limited thereto. The anode may also be Li-metal.

[0117] The above-described positive active material layer may include a positive conductive material and a positive binder together with the positive active material described above.

[0118] At this time, the positive electrode conductive material is used to impart conductivity to the electrode, and in the battery being constructed, any material that has electronic conductivity without causing chemical changes can be used without special limitations. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used.

[0119] In addition, the anode binder serves to improve adhesion between anode active material particles and adhesion between the anode active material and the anode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.

[0120] As a separator, it separates the negative and positive electrodes and provides a pathway for the movement of lithium ions. Any separator typically used in secondary batteries may be used without special restrictions, and it is particularly desirable that it has low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention capacity. Specifically, a porous polymer film, such as a porous polymer film made from a polyolefin-based polymer like ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fiber or polyethylene terephthalate fiber, may be used. Furthermore, a coated separator containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and it may optionally be used in a single-layer or multi-layer structure.

[0121] Examples of the above electrolytes that can be used in the manufacture of lithium secondary batteries include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., but are not limited to these.

[0122] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0123] As the above-mentioned non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyl lactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivative, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivative, tetrahydrofuran derivative, ether, methyl propionate, ethyl propionate, etc. may be used.

[0124] In particular, among the above carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are high-viscosity organic solvents with high dielectric constants that effectively dissociate lithium salts, so they can be used preferably. Furthermore, if low-viscosity, low-dielectric constant linear carbonates such as dimethyl carbonate and diethyl carbonate are mixed with these cyclic carbonates in appropriate proportions, an electrolyte with high electrical conductivity can be produced, making it even more preferable to use.

[0125] The metal salt mentioned above may be a lithium salt, and the lithium salt is a substance that dissolves well in the non-aqueous electrolyte; for example, as the anion of the lithium salt, F - , Cl - , I - , NO3 -, N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more types selected from the group consisting of can be used.

[0126] In addition to the above electrolyte components, the above electrolyte may further include one or more additives for the purpose of improving the lifespan characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery, such as, for example, a haloalkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.

[0127] The lithium secondary battery according to the present invention is useful in portable devices such as mobile phones, laptop computers, and digital cameras, as well as in the field of electric vehicles such as hybrid electric vehicles (HEVs), and can be particularly preferably used as a constituent battery of a medium-to-large battery module. Accordingly, the present invention also provides a medium-to-large battery module comprising such a lithium secondary battery as a unit battery.

[0128] One embodiment of the present invention provides a battery module including the secondary battery as a unit cell and a battery pack including the same. Since the battery module and the battery pack include the secondary battery having high capacity, high rate capability and cycle capability, they can be used as a power source for a medium-to-large device selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.

[0129] Hereinafter, preferred embodiments are presented to aid in understanding the present invention; however, the above embodiments are merely illustrative of the description, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and spirit of the description, and that such variations and modifications fall within the scope of the appended claims.

[0130] <Example>

[0131] Preparation of a primer coating layer

[0132] <Preparation of the first primer coating layer>

[0133] A slurry for forming a primer coating layer was obtained by dissolving a PAM-based binder as a binder and SWCNT as a conductive agent in water at a weight ratio of 95:5. At this time, CMC was used as a dispersant at a ratio of 1.5 times the SWCNT. (Solid content: 5%)

[0134] Next, a slurry for forming the primer coating layer was applied to both sides of a Cu foil current collector with a thickness of 8 μm to a thickness of 0.5 μm, and then vacuum dried at 120°C for 24 hours to form a negative current collector layer having a first primer coating layer.

[0135] <Preparation of the second primer coating layer>

[0136] A slurry for forming a primer coating layer was obtained by dissolving a rubber-based (SBR) binder as a binder and Super-C (Carbon Black) as a conductive agent in a water:IPA = 9:1 solvent at a weight ratio of 30:70. (Solid content: 20%)

[0137] Next, a slurry for forming the primer coating layer was applied to both sides of a Cu foil current collector with a thickness of 8 μm to a thickness of 0.5 μm, and then vacuum dried at 120°C for 24 hours to form a negative current collector layer having a second primer coating layer.

[0138] <Manufacturing of the Cathode>

[0139] Example 1: Preparation of a cathode

[0140] A negative electrode active material layer composition was prepared using Si (average particle size (D50): 8 μm) as a silicon-based active material, SWCNT, and polyacrylamide as a binder in a weight ratio of 89:1:10. A negative electrode slurry was prepared by adding the composition to distilled water as a solvent for forming the negative electrode slurry (solid content 25 wt%).

[0141] For the mixing method, SWCNT, binder, and water were dispersed using a homo mixer at 2500 rpm for 30 min, and then an active material was added and dispersed at 2500 rpm for 30 min to prepare a slurry.

[0142] As a cathode current collector, the cathode slurry is applied at a rate of 2.75 mg / cm² to both sides of an 8 μm thick Cu foil current collector having the aforementioned first primer coating layer formed thereon. 2A cathode was prepared by forming a cathode active material layer (thickness: 33㎛) by coating with a loading amount, roll pressing, and drying in a vacuum oven at 130℃ for 10 hours. (Porosity: 55%)

[0143] In the above Example 1, the same as Example 1 was prepared, except that the negative current collector layer and silicon-based active material of Table 1 below were used.

[0144] cathode current collector Silicon-based active material Si Porosity of the cathode active material layer D50 (㎛) Content (parts by weight) Example 1 Cu foil current collector coated with a first primer coating layer 8 89 55% Example 2 Cu foil current collector coated with a first primer coating layer 5 89 55% Example 3 Cu foil current collector coated with a second primer coating layer 5 89 55% Example 4 Cu foil current collector coated with a first primer coating layer 10 89 60% Example 5 Cu foil current collector coated with a first primer coating layer 12 89 63% Comparative Example 1 Cu foil entire house 5 89 55% Comparative Example 2 Cu foil entire house 8 89 55% Comparative Example 3 Cu foil current collector coated with a first primer coating layer 8 89 35% Comparative Example 4 Cu foil current collector coated with a first primer coating layer 4 89 25% Comparative Example 5 Cu foil entire house 4 89 25% Comparative Example 6 Cu foil entire house 12 89 63%

[0145] Manufacturing of secondary batteries

[0146] LiNi as a positive electrode active material 0.6 Co 0.2 Mn 0.2 An anode slurry was prepared by adding O2 (average particle size (D50): 15㎛), carbon black as a conductive material (product name: Super C65, manufacturer: Timcal), and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming an anode slurry (solid content concentration 78 wt%).

[0147] 537 mg / 25 cm of the anode slurry is applied to both sides of an aluminum current collector (thickness: 12 μm) as an anode current collector. 2 A positive electrode was manufactured by coating with a loading amount, rolling, and drying in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65㎛) (positive electrode thickness: 77㎛, porosity 26%).

[0148] A secondary battery was manufactured by interposing a polyethylene separator between the anode and the cathode of Example 1 and injecting an electrolyte.

[0149] The above electrolyte was prepared by adding vinylene carbonate at 3% by weight based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) were mixed in a volume ratio of 10:90, and adding LiPF6 as a lithium salt at a concentration of 1M.

[0150] Monocells were each manufactured in the same manner as above, except that the cathodes of the above examples and comparative examples were used, and lifespan characteristics were evaluated in the range of 4.2-3.0V.

[0151] Experimental Example 1: Evaluation of Life Characteristics

[0152] For the secondary batteries containing the negative electrodes prepared in the above examples and comparative examples, a lifespan evaluation was conducted using an electrochemical charge / discharger and the capacity retention rate was evaluated. The secondary batteries were subjected to a cycle test at 4.2-3.0V 1C / 0.5C, and the number of cycles at which the capacity retention rate reached 80% was measured.

[0153] Capacity Retention Rate (%) = {(Discharge Capacity in the Nth Cycle) / (Discharge Capacity in the First Cycle)} × 100

[0154] The results were as shown in Table 2 below.

[0155] Experimental Example 2: Measurement and Evaluation of Resistance Increase Rate

[0156] In the above Experimental Example 1, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles during the test, and then the resistance was measured by discharging at 2.5C pulse at SOC50 to compare and analyze the resistance increase rate.

[0157] Regarding the above evaluation of the resistance increase rate measurement, data at 250 cycles was calculated, and the results are as shown in Table 2 below.

[0158] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 SOH 80% (cycle) life characteristic evaluation (4.2-3.0V) 240 235 227 222 219 203 170 216 195 160 148 Resistance increase rate(%, @250cycle, discharge) 45 50 56 63 67 100 250 87 93 >250 >250

[0159] As can be seen in Table 2 above, in the case of the negative electrode for a lithium secondary battery according to the present invention, capacity characteristics were maximized by using a silicon-based active material, and it was confirmed that the output and lifespan characteristics were excellent by using a primer coating layer having a specific composition to improve adhesion to the negative electrode current collector while the negative electrode active material layer satisfies a specific porosity range to simplify the pore structure.

[0160] When the particle size (D50) of the existing silicon-based active material is large, the initial diffusion resistance can be improved; however, due to insufficient adhesion with the negative electrode current collector layer, the resistance increases as the cycle progresses, and the lifespan characteristics deteriorate. Accordingly, the embodiment according to the present application was able to increase the particle size of the silicon-based active material compared to the existing one by applying a primer coating layer.

[0161] That is, it was found that the lifespan characteristics of Examples 1 to 5 were improved compared to Comparative Example 6, which had a large particle size and no primer coating layer applied. In particular, when comparing Comparative Example 6 and Example 5, it was found that although the particle size was the same, the lifespan performance differed depending on the presence or absence of the primer layer.

[0162] In addition, in Table 2 above, a resistance increase rate of >250 indicates a case where resistance measurement is impossible. Generally, resistances of 250% or higher have a high R value, so when a current of 2.5C is applied, it turns off at the safety upper limit voltage, making resistance measurement impossible.

[0163] In conclusion, in the case of Comparative Examples 1, 2, 5, and 6, which do not include a primer coating layer like the present invention, it was confirmed that when an active material with a large particle size is used, volume expansion is significant, and as a result, resistance increases due to reduced adhesion with the negative current collector layer, and consequently, lifespan performance deteriorates. On the other hand, in the case of the example with a primer coating layer, adhesion is improved and diffusion characteristics are also improved, and it was confirmed that the performance characteristics are superior compared to when a silicon-based active material of 5 μm is applied. Explanation of the symbols

[0164] 10: Cathode active material layer 20: Primer coating layer 30: Cathode current collector layer

Claims

Claim 1 A negative electrode for a lithium secondary battery comprising: a negative current collector layer; a primer coating layer comprising a primer coating layer composition provided on one or both sides of the negative current collector layer; and a negative active material layer provided on the opposite side of the primer coating layer that contacts the negative current collector layer; wherein the negative active material layer comprises a negative active material layer composition comprising a silicon-based active material; a negative conductive material; and a negative binder, and the silicon-based active material comprises SiOx (x=0) and SiOx (0 <x<2)로 이루어진 군에서 선택되는 1 이상을 포함하며, 상기 실리콘계 활물질 100 중량부 기준 상기 SiOx (x=0)를 95 중량부 이상 포함하며,상기 프라이머 코팅층 조성물은 바인더; 및 도전재;로 이루어진 군에서 선택되는 1 이상을 포함하며,상기 음극 활물질층의 공극률(porosity)이 50% 이상이며,상기 음극 활물질층에 포함되는 실리콘계 활물질의 D50 입도가 5μm 이상이고,상기 프라이머 코팅층의 두께는 1nm 이상 1μm 이하인 것인 리튬 이차 전지용 음극. Claim 2 delete Claim 3 A negative electrode for a lithium secondary battery according to claim 1, wherein the porosity of the negative electrode active material layer is 60% or more and 90% or less. Claim 4 A negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material included in the negative electrode active material layer has a D50 particle size of 8 μm or more and 15 μm or less. Claim 5 A negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material is 80 parts by weight or more based on 100 parts by weight of the negative electrode active material layer composition. Claim 6 A negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode conductive material comprises one or more selected from the group consisting of a point-type conductive material; a linear conductive material; and a planar conductive material. Claim 7 A negative electrode for a lithium secondary battery according to claim 1, wherein the binder is 10 parts by weight or more and 100 parts by weight or less based on 100 parts by weight of the primer coating layer composition. Claim 8 A negative electrode for a lithium secondary battery according to claim 1, wherein the adhesion force of the surface of the negative electrode active material layer in contact with the primer coating layer satisfies 100gf / 5mm or more and 500gf / 5mm or less under conditions of 25℃ and atmospheric pressure. Claim 9 A negative electrode for a lithium secondary battery according to claim 1, wherein the thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less. Claim 10 A lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to any one of claims 1 and 3 to 9; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Negative electrode and secondary battery comprising the same

    KR1020210060191A

  • Negative electrode current collector for lithium free battery, electrode assembly including the same, lithium free battery

    KR1020210136832A

  • Active material layer for negative electrode and method for manufacturing same, electrode mixture paste for negative electrode of storage device, negative electrode for storage device, and storage device

    KR1020220073791A